Recombinant vaccines for COVID-19 - Tushar Yadav; Nishant Srivastava; Gourav Mishra; Kuldeep Dhama; Swatantra Kumar; Bipin Puri; Shailendra K Saxena (Taylor & Francis Group, 2020)
SARS-CoV-2, the causative agent of COVID-19, has imposed a major public health threat, which needs effective therapeutics and vaccination strategies. Several potential candidate vaccines being rapidly developed are in clinical evaluation. Considering the crucial role of SARS-CoV-2 spike (S) glycoprotein in virus attachment, entry, and induction of neutralizing antibodies, S protein is being widely used as a target for vaccine development. Based on advances in techniques for vaccine design, inactivated, live-vectored, nucleic acid, and recombinant COVID-19 vaccines are being developed and tested for their efficacy. Phase3 clinical trials are underway or will soon begin for several of these vaccines. Assuming that clinical efficacy is shown for one or more vaccines, safety is a major aspect to be considered before deploying such vaccines to the public. The current review focuses on the recent advances in recombinant COVID-19 vaccine research and development and associated issues.